BIMBINGAN KONSELING ISLAM DENGAN TEKNIK KOMUNIKASI TERAPEUTIK UNTUK PENANGANAN LGBT DI SMA DAARUSSA’ADAH GUNUNG MANIK - Raden Desbi Sahaburahaman; Dadang Ahmad Fajar; Lilis Satriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) sexual orientation deviation among adolescents in religious-based school environments requires comprehensive, structured, and humane handling. This study aims to analyze the objective condition of students indicated with LGBT tendencies, evaluate the application of Islamic Counseling Guidance (BKI) using therapeutic communication techniques, assess the results of behavioral changes, and formulate a design for BKI service programs at SMA Daarussa'adah Gunung Manik. This research employs a descriptive qualitative approach with an in-depth case study method. Primary data were gathered through in-depth interviews, passive participative observation, and documentation studies involving Islamic guidance counselors, school leaders, and 8 students undergoing counseling interventions. The results revealed that: (1) The condition of LGBT perpetrators at SMA Daarussa'adah was dominated by lesbian tendencies categorized into three risk triage levels: early symptoms (prodromal), indicated (identified), and severe maladaptive (referral), triggered by childhood sexual abuse trauma, family dysfunction (fatherless), and social media algorithms; (2) BKI implementation integrated five systematic stages (identification, diagnosis, prognosis, treatment, and follow-up) applying 6 Qur'anic verbal communication principles (Qaulan Sadida, Baligha, Ma'rufa, Karima, Layyina, Maysura) and 20 therapeutic communication techniques; (3) The application of BKI therapeutic communication techniques effectively produced significant positive changes, including psychological emotional stability, improved academic discipline and achievement, strengthened spiritual faith, and restored family communication; (4) A BKI program design based on therapeutic communication was formulated as a novel, non-punitive, and rehabilitative counseling model in Islamic schools.